The Influence of Green Tourism Practice, Green Communication and Tourist Green Lifestyle on the Pro-Environmental Behaviour of Tourists at the PIK Mangrove Nature Park - Lusiana Tanuwijaya; Ika Suryono Djunaid (Darul Yasin Al Sys, 2026)
Urban nature-based tourism destinations face increasing environmental pressures, particularly Taman Wisata Alam Mangrove PIK in North Jakarta, which serves conservation, educational, and recreational functions. In mangrove ecosystem tourism, green tourism practices, effective environmental communication, and tourists’ green lifestyles are essential for fostering consistent pro-environmental behaviour. This study aims to analyze the partial and simultaneous effects of Green Tourism Practice, Green Communication, and Green Lifestyle on tourists’ Pro-Environmental Behaviour. A quantitative approach with a descriptive design was employed. Primary data were collected through a four-point Likert-scale questionnaire distributed to 100 domestic tourists aged at least 17 years who had visited Taman Wisata Alam Mangrove PIK within the previous 12 months. Respondents were selected using purposive sampling. Data were analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression, t-tests, F-tests, correlation coefficient analysis, and coefficient of determination analysis with SPSS 25. The findings show that Green Tourism Practice has a positive and significant effect on Pro-Environmental Behaviour, with t = 6.068, Sig. = 0.000, and β = 0.400. Green Communication also has a positive and significant effect, with t = 6.909, Sig. = 0.000, and β = 0.454, making it the most dominant variable in the model. Green Lifestyle has a positive and significant effect, with t = 6.403, Sig. = 0.000, and β = 0.422. Simultaneously, the three independent variables significantly influence Pro-Environmental Behaviour, with F = 45.341, Sig. = 0.000, and R² = 0.586. These findings demonstrate that strengthening green tourism practices, environmental communication, and tourists’ green lifestyles can enhance pro-environmental behaviour in urban mangrove tourism destinations. This study contributes to sustainable tourism literature by providing empirical evidence on behavioural determinants in an urban conservation-based tourism context and offers practical implications for destination managers in designing more effective environmental education, communication, and visitor-engagement strategies.